2014
DOI: 10.1007/s10792-013-9882-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel duplication in the PAX6 gene in a North Indian family with aniridia

Abstract: Mutations in paired box gene 6 (PAX6) are the major cause of aniridia that may be associated with several other developmental anomalies of the eye, including microcornea in rare cases. Therefore, the purpose of this study was to identify the underlying genetic cause in a two-generation North Indian family diagnosed with aniridia. All the participants enrolled in the study, including the aniridia family and 20 healthy individuals (controls), underwent a comprehensive ophthalmic examination. Mutation screening w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Mutation of PAX6 occurred de novo on a paternal chromosome by direct duplication, which presumably created replication slippage or unequal non-sister chromatids exchange during spermatogenesis (28). A novel PAX6 duplication in exon 5 at position c.474dupC was identified by Goswami et al This was a report on a duplication in a North Indian family with autosomal dominant aniridia (29). In a study by Godavova et al (30), aniridia DNA analysis revealed the presence of p.Gln180X PAX6 mutation in all of the affected individuals.…”
Section: Resultsmentioning
confidence: 99%
“…Mutation of PAX6 occurred de novo on a paternal chromosome by direct duplication, which presumably created replication slippage or unequal non-sister chromatids exchange during spermatogenesis (28). A novel PAX6 duplication in exon 5 at position c.474dupC was identified by Goswami et al This was a report on a duplication in a North Indian family with autosomal dominant aniridia (29). In a study by Godavova et al (30), aniridia DNA analysis revealed the presence of p.Gln180X PAX6 mutation in all of the affected individuals.…”
Section: Resultsmentioning
confidence: 99%